Meta-Analysis of Differentially Expressed Genes in the Substantia Nigra in Parkinson’s Disease Supports Phenotype-Specific Transcriptome Changes - Phung, Duong My; Lee, Jinwoo; Hong, SangKyoon; Kim, Young Eun; Yoon, Jeehee; Kim, Yun Joong (Frontiers in Neuroscience, 2020)
Background: Studies regarding differentially expressed genes (DEGs) in Parkinson’s disease (PD) have focused on common upstream regulators or dysregulated pathways or ontologies; however, the relationships between DEGs and disease-related or cell-type enriched genes have not been systematically studied. Meta-analysis of DEGs (meta-DEGs) are expected to overcome the limitations, such as replication failure and small sample size of previous studies. Purpose: Meta-DEGs were performed to investigate dysregulated genes enriched with neurodegenerative disorder causative or risk genes in a phenotype specific manner. Methods: Six microarray datasets from PD patients and controls, for which substantia nigra sample transcriptome data were available, were downloaded from the NINDS data repository. Meta-DEGs were performed using two methods, combining p-values and combing effect size, and common DEGs were used for secondary analyses. Gene sets of cell-type enriched or disease-related genes for PD, Alzheimer’s disease (AD), and hereditary progressive ataxia were constructed by curation of public databases and/or published literatures. Results: Our meta-analyses revealed 449 down-regulated and 137 up-regulated genes. Overrepresentation analyses with cell-type enriched genes were significant in neuron-enriched genes but not in astrocyte- or microglia-enriched genes. Meta-DEGs were significantly enriched in causative genes for hereditary disorders accompanying parkinsonism but not in genes associated with AD or hereditary progressive ataxia. Enrichment of PD-related genes was highly significant in down-regulated DEGs but insignificant in up-regulated genes. Conclusions: Downregulated meta-DEGs were associated with PD-related genes, but not with other neurodegenerative disorders genes. These results highlight disease-phenotype specific changes of dysregulated genes in PD.